Comparison of Physical Fitness Levels between Boarding School Students based on Islamic Boarding School and Formal School Students - Mohamad Da'i; Nurman Ramadhan; Abdul Rohman (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2023)
The rapid development of the social environment has posed significant challenges and influences on educational development in schools. Therefore, education that combines both school and Islamic boarding school (pesantren) is seen as one of the solutions for parents and children to overcome the challenges of the current era. However, the different cultural and educational contexts between schools in pesantren environments and formal schools will certainly have different impacts on the physical fitness of students. This study aims to identify the differences in the level of physical fitness between students at MTs Islamiyah Tulungagung (Islamic boarding school) and students at MTs Al-Falah Gajah (formal school). The population used in this study consisted of 276 students, while the sample size used was 25% of the total population, amounting to 65 students. The research method used was the ex post facto method with a static group comparison approach. The research instrument used was a psychomotor test, specifically the Physical Fitness Test for junior high school/MTs students (aged 13-15 years), which included: a) 60-meter sprint, b) pull-ups, c) sit-ups for 30 seconds, d) vertical jump, and e) Multistage Fitness Test (MFT). The results showed a significant difference in the average level of physical fitness between the students of MTs Islamiyah Tulungagung with a total average of 61.88 and the students of MTs Al-Falah Gajah with an average of 60.75. Thus, the level of physical fitness of students at MTs Islamiyah Tulungagung was better compared to MTs Al-Falah Gajah.